2002
DOI: 10.1021/bc015563u
|View full text |Cite
|
Sign up to set email alerts
|

Tat Peptide Directs Enhanced Clearance and Hepatic Permeability of Magnetic Nanoparticles

Abstract: Superparamagnetic nanoparticles have a number of important biomedical applications, serving as MR contrast agents for imaging specific molecular targets, as reagents for cell labeling and cell tracking, and for the isolation of specific classes of cells. We have determined the physical and biological properties of MION-47 and amino-CLIO, nanoparticles which serve as precursors for the synthesis of targeted MR contrast agents, and Tat-CLIO, a nanoparticle used as a cell labeling reagent. Blood half-lives for MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
168
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(171 citation statements)
references
References 15 publications
3
168
0
Order By: Relevance
“…3a and Table 1). [17] NWs extracted from the bloodstream after 24 h retained their original shape (Supporting Information Fig. 4) and they showed a slight increase in hydrodynamic size (from ca.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3a and Table 1). [17] NWs extracted from the bloodstream after 24 h retained their original shape (Supporting Information Fig. 4) and they showed a slight increase in hydrodynamic size (from ca.…”
mentioning
confidence: 99%
“…Dextran-coated magnetic iron oxide (IO) nanoparticles are of particular interest because they show relatively low toxicity and long circulation, and dramatically enhance hydrogen T 2 relaxation in magnetic resonance imaging (MRI). [5,11,[15][16][17][18][19][20] The clinical power of these materials may be amplified by improving MRI relaxivity, blood circulation times, and the homing of such nanoparticles to tumors. Efforts to increase MRI sensitivity have focused on development of new magnetic core materials, [6,12] or on improvements in nanoparticle size [21] or clustering.…”
mentioning
confidence: 99%
“…Previous studies have reported uptake of dextrancoated nanoparticles ranging from 0.011 to 0.118 pg of iron per cell (usually after 1 hr of incubation) by various tumor cells, and a maximum load of 0.97 pg in primary isolated mouse peritoneal macrophages (19,20). The use of an HIV-1 transactivator (Tat) peptide sequence, for example, can increase their uptake by lymphocytes more than 100-fold compared to untagged nanoparticles (21,22), permitting in vivo tracking of labeled cells (23)(24)(25). Other approaches to increase cellular uptake include receptor-mediated endocytosis, the use of carrier transporters as magnetodendrimers (26,27), and transfection methods combined with simple incubation (28,29).…”
mentioning
confidence: 99%
“…Monocrystalline iron oxide nanoparticle (MION)-47 consists of USPIO particles coated with dextran and has a relaxivity R1 of about 21.9 mmol À1 Á sec À1 and a relaxivity R2 of about 44.6 mmol À1 Á sec À1 at 0.47 T, 37 C in water (12). The concentration of iron in USPIO agent is 11.22 mg/mL contained in 20 mmol NaCitrate at pH 8.…”
Section: Mr Contrast Materialsmentioning
confidence: 99%